Role of Universities in Make in India Some points to Ponder - S M Misal; Rajkumari Tamphasana (2018)
today Universities are considered as centre of attraction. It is rightly said by then Prime Minister Lt. Pandit Jawwaharlal Nehru as- Universities are the temples of knowledge. no country or society can prosper without developing a right culture which promotes knowledge and research. It is the only centre which can ignite the quest for knowledge. It is the place which promotes the spirit of excellence and developmental approach. It is the institution that gave inspirational climate for promotion of scientific temperament and research of knowledge.
Keywords: Education